1D Coordination π–d Conjugated Polymers with Distinct Structures Defined by the Choice of the Transition Metal: Towards a New Class of Antiaromatic Macrocycles. Issue 1 (3rd November 2020) - Santhini, Vijai M.; Wäckerlin, Christian; Cahlík, Aleš; Ondráček, Martin; Pascal, Simon; Matěj, Adam; Stetsovych, Oleksandr; Mutombo, Pingo; Lazar, Petr; Siri, Olivier; Jelínek, Pavel
Abstract: Recently π–d conjugated coordination polymers have received a lot of attention owing to their unique material properties, although synthesis of long and defect‐free polymers remains challenging. Herein we introduce a novel on‐surface synthesis of coordination polymers with quinoidal ligands under ultra‐high vacuum conditions, which enables formation of flexible coordination polymers with lengths up to hundreds of nanometers. Moreover, this procedure allows the incorporation of different transition‐metal atoms with four‐ or two‐fold coordination. Remarkably, the two‐fold coordination mode revealed the formation of wires constituted by (electronically) independent 12‐membered antiaromatic macrocycles linked together through two C−C single bonds. Abstract : The on‐surface synthesis approach under UHV conditions has led us to the formation of 1D coordination π–d conjugated polymers on metal surfaces. The reaction of quinoidal ligand with different transition metals results in two distinct coordination motifs: four‐fold (Cr, Fe, Co, Ni) and two‐fold (Cu). The backbone of the Cu‐coordinated 1D chain is formed by antiaromatic 12‐membered macrocycles.